1 - Études archéologiques du peuplement de la moyenne vallée du fleuve Sénégal : résultats depuis les années 90 - Alioune Dème (Afrika Zamani, 2022)
This article summarizes the results of archaeological research carried out in the middle valley of the Senegal River since the 1990s. The Middle Valley of the Senegal River has a rich and diverse ecology. This area of abundance, in a Sahelian context, attracted very early populations that were victims of fluctuations in the isohyet 400 mm. Oral tradition and Arab sources affirm that the area was dominated by states such as the Tekrour and Silla which played a great role in the Islamization of West Africa. Because of its history and the presence of hundreds of archaeological sites, archaeological researches have been conducted in the middle valley of the Senegal River since 1916. It was not until the 1990s with the MSV (Middle Senegal Valley) Project that the beginning of a regional and processual approach was seen. These years also mark the introduction of the archaeomagnetic curve and the use of flotation in Senegalese archaeology.